A False Start? British Perspectives on Italy's Participation in the Early Phases of the European Economic Integration Process: The Case of the OEEC (1948–1952). Issue 1 (2nd January 2020) - Ventresca, Roberto
Abstract: This article examines how Anglo-Italian relationships unfolded in the aftermath of the Second World War within the framework of the Organization for European Economic Cooperation (OEEC). By analysing Italy's participation in the early stages of the European integration process through the lens of British diplomacy, this contribution aims to shed new light on the international dimension of Rome's post-1945 political and economic strategies. First, the article considers the main concerns that characterized Italy's involvement in the OEEC activities between the late 1940s and the early 1950s: the promotion of the circulation of the intra- and extra-European manpower and the liberalization of trade and payments. Second, rather than making a 'classic' comparison between the divergent policies – particularly the internal and international economic programmes – that Britain and Italy pursued within the OEEC, this article highlights the extent to which an 'asymmetry of power' impacted Italy's ability to realize its strategies. To conclude, the essay assesses how bilateral and multilateral relationships in the OEEC arena mutually contributed to the shaping of Italy and Britain's patterns of post-WWII economic reconstruction.